Analisa Dan Perancangan Sistem Informasi Akuntansi Zakat Penghasilan Pegawai Negeri Sipil - Eva Nurfazilla; Ulan Ulan; Nurul Pahana; Desi Nurhazana; Decky Hendarsyah (LPPM ISNJ Bengkalis, 2019)
This research aims to analyze and design a zakat accounting information system at the Bengkalis District National Amil Zakat Board which is not well systemized. At the same time to design the management of income zakat for Civil Servants of Bengkalis Regency in accordance with the Bengkalis Regency Regional Government's plans regarding Regional Regulations on Zakat. Data collection techniques used were observation, interviews, documentation and literature study. In carrying out system design activities database design techniques, system design and user interface design are used. With this system design is able to answer the needs of the general public, especially for Civil Servants in Bengkalis Regency and provide transparency in the management of zakat, infaq and alms funds through financial reports that can be accessed by the public.